Effect of exogenous application of phytohormones and fungicides on yield, quality storability and economics of garlic (Allium sativum L.) - Ram, Munshi; Kumar, Satesh; Chopra, Sandeep; Kumar, Manoj; Gupta, RK (Vegetable Science, 2018)
In garlic, compactness, firmness and healthy state are important quality attributes that determine market value and consumer preference. Phytohormones (cycocel and ethrel) and fungicides (carbendazim and benomyl) are known to play important role in checking post-harvest losses like physiological weight in loss (PLW), rotting, sprouting etc in long stored crops. Main aim of the study was to investigate the effects of their preharvest application on growth, yield, quality and storability of garlic cv. Agrifound Parvati. Results suggested that exogenous application of CCC at 1000 ppm applied at 90 days (bulb development stage) and 150 days (50% neck fall stage) significantly increased growth and yield related parameters in garlic. This hormone maintained higher levels of sulphur content after harvest, which proved helpful in reducing PLW of bulbs significantly during ambient storage period of 4 months. Economically, cost benefit ratio in this treatment was high, both at harvest and after storage as compared to other treatments and control. Fungicides on the other hand, had more or less similar effect on growth and yield parameters but showed significant effect on post-harvest losses of garlic as compared to control. Hence, application of CCC at critical stages of alliums can be tried for reducing postharvest losses during long periods of ambient storage.